Description of Therapeutic Communication of Midwives in Assisting with Childbirth at the Partner Clinic of the Santa Elisabeth Health Sciences College, Medan, 2019 2025 - Panjaitan, Intan Aprillia; Oktaviance, R.; Veronika, Anita (Science: Indonesian Journal of Science, 2026)
Therapeutic communication is a crucial aspect of midwifery care that helps laboring mothers feel more comfortable, reduces anxiety, and facilitates the healing process. Ineffective communication may negatively impact a mother's birthing experience. Objective: This study aims to describe the therapeutic communication of midwives in labor assistance at affiliated clinics of Santa Elisabeth School of Health Sciences Medan in 2025. Methods: This descriptive study involve 30 midwives from affiliated clinics using total sampling. Data are collected using a questionnaire as the primary instrument. Results: The results showed that most midwives have good therapeutic communication (76.7%), moderate (20%), and poor (3.3%). Communication is also influenced by age and length of work experience.Conclusion: The majority of midwives in affiliated clinics demonstrated good therapeutic communication during labor assistance. Ongoing training is needed to enhance communication skills, especially for midwives with less work experience